2021
DOI: 10.2147/idr.s296054
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Community Origin Escherichia coli and Klebsiella pneumoniae Uropathogenic Strains Resistant to Antibiotics in Franceville, Gabon

Abstract: Introduction Urinary tract infection is one of the major causes of consultation, microbiologic exploration, intensive use of antibiotics worldwide, and the second leading cause of clinical consultation in community practice. Many bacteria play a role in the urinary tract infections etiology, including Enterobacteriaceae such as Escherichia coli ( E. coli ) and Klebsiella spp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
9
6
1
Order By: Relevance
“…This higher resistance rate could be explained by the excessive parenteral administration of these antibiotics in our region. Our study explored a high resistance rate, ranging from 72.3 to 85.1%, against TGC antibiotics, which was in agreement with previous researches conducted by Raeispour et al [ 25 ] and Lee et al [ 33 ], but in contrast to findings achieved from USA [ 24 ] and Gabon [ 30 ]. The high resistance rates against TGCs is possibly rooted in increasing the spread of extended-spectrum β-lactamase genes in UTI pathogens in Iran and other countries during recent decades, which were not investigated in the current study [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This higher resistance rate could be explained by the excessive parenteral administration of these antibiotics in our region. Our study explored a high resistance rate, ranging from 72.3 to 85.1%, against TGC antibiotics, which was in agreement with previous researches conducted by Raeispour et al [ 25 ] and Lee et al [ 33 ], but in contrast to findings achieved from USA [ 24 ] and Gabon [ 30 ]. The high resistance rates against TGCs is possibly rooted in increasing the spread of extended-spectrum β-lactamase genes in UTI pathogens in Iran and other countries during recent decades, which were not investigated in the current study [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Of the three aminoglycosides studied here, AMK showed the highest efficacy compared to GEN and TOB, supporting previous studies from USA [ 24 ] and Gabon [ 30 ]. However, a survey by Kushwaha et al [ 31 ] from Nepal showed an opposite result: GEN had higher efficacy against UTI-inducing E .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations